The molecular and phenotypic basis of the glioma invasive perivascular niche - Diksin, Mohammed; Smith, Stuart J.; Rahman, Ruman (MDPI, 2017)
Gliomas are devastating brain cancers that have poor prognostic outcomes for their patients. Short overall patient survival is due to a lack of durable, efficacious treatment options. Such therapeutic difficulties exist, in part, due to several glioma survival adaptations and mechanisms, which allow glioma cells to repurpose paracrine signalling pathways and ion channels within discreet microenvironments. These Darwinian adaptations facilitate invasion into brain parenchyma and perivascular space or promote evasion from anti-cancer defence mechanisms. Ultimately, this culminates in glioma repopulation and migration at distances beyond the original tumour site, which is a considerable obstacle for effective treatment. After an era of failed phase II trials targeting individual signalling pathways, coupled to our increasing knowledge of glioma sub-clonal divergence, combinatorial therapeutic approaches which target multiple molecular pathways and mechanisms will be necessary for better treatment outcomes in treating malignant gliomas. Furthermore, next-generation therapy which focuses on infiltrative tumour phenotypes and disruption of the vascular and perivascular microenvironments harbouring residual disease cells offers optimism for the localised control of malignant gliomas.